Baseline haemoglobin and thromboelastometry are predictive of red blood cell requirements and one-year mortality in liver transplantation. (December 2021) - Viguera, Laura; Blasi, Annabel; Reverter, Enric; Arjona, Begoña; Caballero, Marta; Chocron, Ivette; García-López, José Antonio; Gutierrez, Rosa; Martin, Maria Jesús; Pérez-Peña, Jose; Pitera, Javier; Zarragoikoetxea, Iratxe; et al.
Abstract: Background: To determine the predictive capacity of baseline haemoglobin and maxim clot firmness (MCF) EXTEM thromboelastometry for intraoperative red blood cell (RBC) requirements and its influence on mortality. Methods: 591 adult liver transplant (LT) recipients from ten Spanish centres were reviewed. The main outcomes were the percentage of patients who received RBC and massive transfusion (≥ 6 RBC units), RBC units transfused, and mortality. Results: 76 % received a donor after brain death graft and 24 % a controlled donor after circulatory death graft. Median (interquartile ranges) RBC transfusion was 2 (0–4) units, and 63 % of patients were transfused. Comparing transfused and non-transfused patients, mean (standard deviation) for baseline haemoglobin was 10.4 (2.1) vs. 13.0 (1.9) g/dl (p = 0.001), EXTEM MCF was 51(11) vs. 55(9) mm (p = 0.001). Haemoglobin and EXTEM MCF were inversely associated with the need of transfusion odds ratio (OR) of 0.558 (95 % CI 0.497–0.627, p < 0.001) and OR 0.966 (95 % CI0.945–0.987, p = 0.002), respectively. Pre-operative baseline haemoglobin ≤ 10 g/dL predicted RBC transfusion, sensitivity of 93 % and specificity of 47 %. Massive transfusion (MT) was received by 19 % of patients. Haemoglobin ≤10 g/dL predicted MT with sensitivity 73 % and specificity of 52 %. One-year patient and graft survival were significantly lower in patients who required MT (78 % and 76 %, respectively) vs. those who did not (94 % and 93 %, respectively). Discussion: whereas EXTEM MCF is less dreterminant predicting RBC requirements, efforts are required to improve preoperative haemoglobin up to 10 g/dl in patients awaiting LT.